Resisting Meritocracy and Reappropriating Games: Rhetorically Rethinking Game Design - Paul, Christopher (AoIR Selected Papers of Internet Research, 2013)
Using tools derived primarily from rhetorical analysis and criticism, this project analyzes the impact of the overwhelming focus on balance in video game design. Balance is a central ordering principle of games that is established by designers, praised by gamers, and particularly sought after in multiplayer games. A focus on balance limits games and establishes them as meritocratic spaces, where the ‘best’ players should be the most successful. By establishing a connection between balance and meritocracies it is possible to identify possible locations for resistance to existing norms. Drawing from sociological critiques of meritocracies and current dynamics in game culture, game studies can help reappropriate elements of game design and contribute to a more positive, inclusive game culture.